Performance of i-STAT Point-of-Care Analyser Cartridges After Ambient and Subzero Temperature Exposure. Issue 4 (December 2016) - Fortgens, Philip H.; du Toit, Leon; Hofmeyr, Ross; Dyer, Robert A.; Swanevelder, Justiaan L.
Abstract : Abstract: Point-of-care testing is becoming common practice in a variety of settings, including extreme environments. Little is known about the functioning of these platforms under challenging conditions. The i-STAT (Abbott, Princeton, NJ) is a cartridge-based point-of-care system for the testing of whole blood. This pilot study compares the performance of i-STAT cartridges after exposure to several storage temperatures. The cartridges assessed test for a spectrum of common chemical analytes (Chem8+ cartridge), blood gas analytes (CG4+ cartridge), and a peptide (BNP cartridge). Cartridges were allocated to 4 intervention groups: storage at 2°C to 8°C (manufacturer's instructions), at room temperature, freezing (−20°C), or alternating freeze-thaw cycles. A temperature data logger monitored temperature variations in the refrigerated and freeze-thaw groups. At the end of the intervention period, levels 1 and 3 i-STAT control materials were analyzed using the stored cartridges. Analytical performance was assessed by comparing results to biological variation-derived total allowable error limits. Measurements of all analytes, regardless of storage conditions, were found to be within the manufacturer's acceptable ranges for the control material. Total allowable error was exceeded by 4 analytes at the level 1, and 1 at level 3 controls, respectively. Storage at room temperature and freeze-thawing each accounted for 3 episodes, while storage at 2°C to 8°C and freezing accounted for one each. None of these episodes were considered clinically relevant. The performance of the i-STAT Chem8+, CG4+, and BNP cartridges is not significantly affected when stored under ambient or subzero temperatures. Further study is required, with the inclusion of patient samples.